Hedge funds, financial intermediation, and systemic risk - John Kambhu; Til Schuermann; Kevin J. Stiroh (Federal Reserve Bank of New York, 2007)
Hedge funds are significant players in the U.S. capital markets, but differ from other market participants in important ways such as their use of a wide range of complex trading strategies and instruments, leverage, opacity to outsiders, and their compensation structure. The traditional bulwark against financial market disruptions with potential systemic consequences has been the set of counterparty credit risk management (CCRM) practices by the core of regulated institutions. The characteristics of hedge funds make CCRM more difficult as they exacerbate market failures linked to agency problems, externalities, and moral hazard. While various market failures may make CCRM imperfect, it remains the best line of defense against systemic risk.
Keywords: G12; G21; 330; banks; counterparty credit risk management; liquidity; Hedgefonds; Finanzintermediär; Kreditrisiko; Systemrisiko